Differences In HbA1c Levels In Diabetes Mellitus Patients Using Capillary And Venous blood Samples - Aristoteles; bastian; Teni Lestari (Fakultas Kesehatan IKesT Muhammadiyah Palembang, 2023)
Introduction: HbA1c is a non-enzymatic binding of glucose molecules to hemoglobin through a post- translational glycation process, measuring the level or percentage of glucose bound to hemoglobin, this parameter is used as the main benchmark for controlling Diabetes Mellitus because HbA1c can describe blood sugar levels within a period of 1- 3 months due to red blood cells bound by glucose molecules. HbA1c examination is an examination of glycemic levels which is useful to determine long-term glycemic control in patients with Diabetes Mellitus. From this study to determine differences in HbA1c levels in diabetes mellitus patients using capillary and venous blood samples. Method: Cross-sectional, this research was conducted at the Hematology Laboratory of the Palembang Muhammadiyah Institute of Health and Technology. The population taken was Diabetes Mellitus Patients in the Muhammadiyah Palembang Hospital laboratory. The sample used in this study was 29 samples using purposive sampling. Results: The average HbA1c level was found in 7.91% capillary blood and 7.91% venous blood. Discussion: The conclusion in this study is that capillary and venous blood sampling can be used to check HbA1c levels.